Cardiac electrophysiological imaging systems scalable for high-throughput drug testing - Lee, P; Wang, K; Woods, C; Yan, P; Kohl, P; Ewart, P; Loew, L; Terrar, D; Bollensdorff, C (2012)
Multi-parametric electrophysiological measurements using optical methods have become a highly valued standard in cardiac research. Most published optical mapping systems are expensive and complex. Although some applications demand high-cost components and complex designs, many can be tackled with simpler solutions. Here, we describe (1) a camera-based voltage and calcium imaging system using a single 'economy' electron-multiplying charge-coupled device camera and demonstrate the possibility of using a consumer camera for imaging calcium transients of the heart, and (2) a photodiode-based voltage and calcium high temporal resolution measurement system using single-element photodiodes and an optical fibre. High-throughput drug testing represents an application where system scalability is particularly attractive. Therefore, we tested our systems on tissue exposed to a well-characterized and clinically relevant calcium channel blocker, nifedipine, which has been used to treat angina and hypertension. As experimental models, we used the Langendorff-perfused whole-heart and thin ventricular tissue slices, a preparation gaining renewed interest by the cardiac research community. Using our simplified systems, we were able to monitor simultaneously the marked changes in the voltage and calcium transients that are responsible for the negative inotropic effect of the compound.